PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada karyawan Kantor Cabang Utama Bank Jateng) - Wulandari, Tri; Ratnawati, Intan (Diponegoro Journal of Management, 2019)
This study aims to determine the effect of transformational leadership style variables and organizational culture on performance through job satisfaction as a mediator. This research was conducted at a banking company in the city of Semarang, namely the Main Branch of Bank Jateng. In this study using various data sources in the form of primary data and secondary data.This study uses census techniques, so that the entire population in this study were made respondents. The research questionnaire was distributed to 58 employees of the Main Branch of Bank Jateng. Data analysis techniques in this study is using the SmartPLS 3.2.8 application to determine the path coefficient and the direct or indirect influence of exogenous variables on endogenous variables.The results of this study indicate that the transformational leadership style has a positive and significant effect on the performance of employees and job satisfaction. Organizational culture has a positive and significant effect on employee performance and job satisfaction. In addition, it can be seen that the variable job satisfaction can mediate an indirect relationship between transformational leadership style on employee performance and organizational culture on employee performance.